Early life histories at medieval Mikulčice (ninth–tenth centuries AD, Czechia) based on carbon and nitrogen profiles of tooth dentine - Drtikolová Kaupová, Sylva; Brůžek, Jaroslav; Hadrava, Jiří; Mikšík, Ivan; Morvan, Marine; Poláček, Lumír; Půtová, Lenka; Velemínský, Petr (My University, 2024)
In order to compare the early life experiences of different population subgroups from the Early Medieval center of Mikulčice, carbon and nitrogen isotopic values were measured in dentine serial sections from the first permanent molar of 78 individuals. Age at death, sex (estimated in subadults with the help of proteomics), and socio-economic status were considered explicative variables. Average values of both nitrogen and carbon maximal isotopic offset within the isotopic profile were 3.1 ± 0.8‰ for Δ15Nmax and 1.6 ± 0.8‰ for Δ13Cmax. Individuals who died during the first decade of life showed earlier ages at the stabilization of the nitrogen isotopic curve (suggesting complete weaning) than older individuals. Most individuals (n = 43) showed positive covariance between δ15N and δ13C values during the period of breastfeeding. The average δ15N values from the post-weaning period were similar to those of bone, while post-weaning δ13C values were significantly higher. Though an increased Δ15Nmax may potentially be evidence of physiological stress, the intra-population comparison of early life experiences does not suggest that individuals who died during their first decade experienced greater levels of environmental stress during infancy. The predominance of positive covariance between carbon and nitrogen isotopic values during the breastfeeding period, together with an increased Δ13Cmax and increased post-weaning δ13C, suggests that millet either was a part of a special diet preferred during lactation or was introduced as a first dietary supplement.
Rané dějiny života ve středověkých Mikulčicích (9.-10. stol. n. l.), Česko) na základě uhlíkových a dusíkových profilů zubního dentinu
Keywords: breastfeeding; physilogical stress; diet; stable isotopes; middle ages; central europe